Analysis of The Role of Cipayung Plus Advocacy In Overseeing The Constitutional Court's Decision Regarding Power Restrictions And Public Participation - Rachel Dwita Maharani (Journal of Law, Politic and Humanities, 2026)
The Constitutional Court has a position as the guardian of the constitution in maintaining the principle of limitation of power and ensuring that the administration of the state runs in accordance with constitutional values. In this matter, Constitutional Court Decision No. 90/PUU-XXI/2023 has sparked debate over the age requirements for presidential and vice presidential candidacy. The ruling affirms the minimum age limit for presidential and vice presidential candidates at 40 years old. Still, it provides exceptions for individuals who are or have been elected, including regional heads. The implications are not only related to the technical issue of candidacy requirements but also to electoral justice, the distribution of political opportunities, and the potential concentration of power in certain political circles. Several studies show a decline in democracy, where formal democratic institutions continue to operate but produce an elitist pattern of power consolidation and tend to be exclusive to actors close to the center of power. This situation reaffirms students' strategic position as actors who perform the function of constitutional social control. Students, through a network of intra-, extra-, and coalition organizations such as Cipayung Plus, not only act as a mass of action but also as an epistemic community that conducts advocacy grounded in legal arguments and policy studies. This role directs students to serve as guardians of public morality and rationality in upholding the principle of equality of political rights and the limitation of power.